Assessment of Protective Mechanisms against Ultra Violate–B Elevation in Tow Species of Palms Seedling Grown Under Laboratory Conditions - S, Sajeda Y.; Almusawi, Abdulminam Hussien; A., Eman M. (Journal of Kerbala for Agricultural Sciences, 2020)
The present study was carried out for examining the alterations of total chlorophyll and antioxidants contents (carotenoids, phenols and proline), on two species of palm seedlings, Date palm (Phoenix dactylifera L.) and Washingtonian palm (Washingtonia filifera induced by exposure to UV-B radiations at different periods (2,4,8 and 10 hrs/day). Results showed that the 30 days of UV-B treatment for 2 and 4 hrs./ day caused significantly increased in total chlorophyll contents of both palm seedling species. While the lowest contents of chlorophyll were obtained in plants grown under UV-B radiation stress for 10 hrs./day. On the contrary, the highest value of carotenoids content was recorded after 8 hrs./day of treatment with UV, then it reduced after treated with 10 hrs./day. Similarly, the content of total phenol and proline showed significantly increased with increasing time of UV-B exposed in both species. The study also revealed a significant difference between two palm species in terms of tolerance to UV-B, where it was found that the Date palm (Phoenix dactylifera L.) seedlings were more resistance to such radiation than (Washingtonia filifera ).